Peran Majelis Ta’lim Kanzul Ulum dalam Meningkatkan Pengetahuan Keagamaan di Kelurahan Karyamulya Kota Cirebon - Tosuerdi Tosuerdi; Tuti Alawiyah; Teguh Ragil Priyono (Jurnal Budi Pekerti Agama Islam, 2025)
Based on the research results, it can be concluded that the activities of the Majelis Ta'lim Kanzul Ulum cover three main areas: education, da'wah, and social service. In the field of education, the Majelis regularly holds daily religious studies, monthly religious studies, and special religious studies on Islamic holidays. In the field of da'wah, it coordinates Rebana training and manages Rebana groups, organizes Salawat Dibaiyah meetings, organizes infaq collections for those who wish to contribute, and facilitates Qurban savings programs. Meanwhile, in the social field, the Majelis plays an active role by organizing assistance for orphans and the poor, providing ta'jil, breaking the fast, and sahur during the month of Ramadan, and holding collective celebrations such as Eid al-Adha. These activities show that the Majelis Ta'lim Kanzul Ulum functions not only as a place to learn religion but also as a center for social solidarity and community empowerment. The role of the Majelis Ta'lim Kanzul Ulum in improving religious knowledge in Karyamulya District, Cirebon City, is very significant. This Majelis functions as a forum for fostering and developing religious knowledge, especially in the field of morals. This assembly also serves as a space for the intellectual and practical dimensions of religious life, fostering social piety, encouraging adherence to Islamic teachings, and strengthening the internalization of Quranic values among its congregation. For adolescents in particular, this Majelis Ta'lim provides a foundation for moral awareness, which grows from continuous exposure to religious knowledge and practices. This study also identified supporting and inhibiting factors that influence the effectiveness of the Majelis Ta'lim. Supporting factors include regular evening recitation activities, local government support, regular scheduling, strong organizational management, tolerance within the community, and the provision of food during the events.